Entretien sur le genre. Éléments pour un lexique homosexuel
The following text is a fictional conversation between Maxim, the fictional alter ego of an Antwerp doctoral student, and Corydon, the loving shepherd of Virgil’s Bucolics. The conversation is a possible text where questions of identity, sexuality and gender are discussed in a loose way.